APLIKASI PEMUPUKAN TERHADAP PERTUMBUHAN DAN PRODUKSI DUA VARIETAS BAYAM (Amaranthus sp.) - Yusri Fefiani; Arman D. Dalimunthe (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to determine the growth and yield production of 2 spinach variety on fertilizers application. The design used was split plot design with the first factor is spinach variety namely V1 and V2 and the second factor is the provision fertilizer namely P1 and P2. Variables measured result were growth persentation, plant height, number of leaf, planting leaf weight, planting root weight, planting steam weight. The result fertilizer application has significant effect on the variables of spinach variety, but another variables as plant height, number of leaf, leaf weight, root weight and steam weight weren’t significant effect. Keywords : spinach variety, fertilizer application, growth and production